номер 93 гдз 8 класс алгебра Муравин Муравин

1)\begin{equation}\frac{ax+b}{bx}+\frac{bx-a}{ax}= \end{equation} \begin{equation}=\frac{a^{2}x+ab+b^{2}x-ab}{abx}= \end{equation} \begin{equation}=\frac{a^{2}x+b^{2}x}{abx}=\frac{x\left ( a^{2}+b^{2} \right )}{abx}= \end{equation} \begin{equation}=\frac{a^{2}+b^{2}}{ab} \end{equation} 2)\begin{equation}\frac{c+ny}{cy}-\frac{n-cy}{ny}= \end{equation} \begin{equation}=\frac{nc+n^{2}y-nc+c^{2}y}{cny}= \end{equation} \begin{equation}=\frac{n^{2}y+c^{2}y}{cny}=\frac{y\left ( n^{2}+c^{2} \right )}{cny}= \end{equation} \begin{equation}=\frac{n^{2}+c^{2}}{cn} \end{equation} 3)\begin{equation}\frac{m}{n}+\frac{n}{m}-\frac{\left ( m-n \right )^{2}}{mn} \end{equation} \begin{equation}\frac{m^{2}+n^{2}-m^{2}+2mn-n^{2}}{mn}= \end{equation} \begin{equation}=\frac{2mn}{mn}=2 \end{equation} 4)\begin{equation}\frac{\left ( x-y \right )^{2}}{xy}-\frac{x}{y}-\frac{y}{x} \end{equation} \begin{equation}\frac{x^{2}-2xy+y^{2}-x^{2}-y^{2}}{xy}= \end{equation} \begin{equation}=\frac{-2xy}{xy}=-2 \end{equation} 5)\begin{equation}\frac{a+b}{2ab}+\frac{a+c}{2ac}+\frac{b+c}{2bc} \end{equation} \begin{equation}\frac{ac+bc+ab+bc+ab+ac}{2abc}= \end{equation} \begin{equation}=\frac{2ac+2bc+2ab}{2abc}= \end{equation} \begin{equation}=\frac{2\left ( ac+bc+ab \right )}{2abc}= \end{equation} \begin{equation}=\frac{ac+bc+ab}{abc} \end{equation} 6)\begin{equation}\frac{y+z}{yz}-\frac{x-y}{xy}-\frac{x-z}{xz} \end{equation} \begin{equation}\frac{xy+xz-xz+yz-yx+yz}{xyz}= \end{equation} \begin{equation}=\frac{2yz}{xyz}=\frac{2}{x} \end{equation}
Play
Play
previous arrow
next arrow
Slider